A78 COMPARISON OF THE NICE, SANO, AND WASP CLASSIFICATIONS FOR OPTICAL DIAGNOSIS OF SMALL COLORECTAL POLYPS. (26th February 2020) - Djinbachian, R; Pohl, H; Marchand, E; Marques, P; Bouin, M; Deslandres, E; Weber, A; Bouchard, S; Leduc, R; Von Renteln, D
Abstract: Background: Optical diagnosis can be used as an alternative to pathology for the evaluation of colorectal polyps. There exist multiple classification systems that can be used to assist in performing optical diagnosis. Aims: The aim of this study was to compare three different optical diagnosis classifications (NICE, SANO and WASP) when using Optivista and iScan image enhanced endoscopy (IEE). Methods: The study included subjects between 45–80 years undergoing an elective screening, surveillance, or diagnostic colonoscopy with optical diagnosis using Optivista or iScan IEE. Three validated IEE scales (NICE, SANO and WASP classifications) were used for all optical diagnoses. Primary outcome was the agreement with pathology for surveillance intervals determined when using NICE, SANO and WASP for polyps 1-10mm. Secondary outcomes for polyps 1-10mm included accuracy of polyp diagnosis and negative predictive value (NPV) for rectosigmoid adenomas. Results: A total of 399 patients were prospectively enrolled in the trial. The polyp detection and adenoma detection rates were 58.6% and 38.8% respectively. The proportion of correct surveillance interval assignment when at least one optical diagnosis was made was 92.9% when using NICE, 92.3% when using SANO, 89.5% when using WASP (p=0.656). Correct diagnosis was made for 74.2% of polyps when using NICE, 74.2% when using SANO, 65.6% when using WASP (p=0.012). The NPV for rectosigmoid adenomas was 91.2% when using NICE, 90.5% when using SANO, 87.5% when using WASP. Conclusions: For optical diagnosis using Optivista and iScan IEE, all studied classifications performed equally for surveillance interval assignment. WASP had lower proportion of correct diagnoses on a polyp level and lower NPV for rectosigmoid adenomas. Funding Agencies: None